Diversity and taxonomy of the intertidal patellogastropod limpets of the mainland Indian coastline - Vakani, Bhavik; Nakano, Tomoyuki; Kundu, Rahul (Zootaxa, 2020)
We report the diversity, distribution and taxonomy of patellogastropod species from the entire mainland Indian coastline. A total of 77 coastal areas with rocky outcrops in the sandy shoreline, covering the entire mainland Indian coastline, were surveyed seasonally (four times a year) during December 2014 to December 2016. Coastal habitat characteristics and the diversity of all groups of limpets from the intertidal areas were recorded. Specimens were identified by external morphological shell and gill characteristics, by the colour of the foot, mantle fringe and radular characteristics. Ecological aspects like habitat preference were also used to distinguish species. Existing diagnostic characters were amended with newer characteristics emerged in our study. Seven species from two families, Nacellidae and Lottiidae, were found along the mainland Indian coastline. Each species is present with several polymorphic forms with different colour banding patterns. Our study revealed distinct variations in the radular teeth at the genus level, but less differences within genera. Patellogastropod diversity was greater along the west coast of India and only Cellana rota was available throughout the mainland Indian coastline.